The Global ELT coursebook: A case of Cinderella's slipper?. (October 2022) - Mishan, Freda
Abstract : English language teaching (ELT) publishing as we know it today has a long and lucrative history, dating, according to Rix (2008), from the Longman publication of Michael West's New Method Readers in 1926, to the present day, where annual turnover runs to around US194 billion (Jordan & Gray, 2019). Some of the sector's best-sellers, such as Oxford University Press's Headway series (Soars & Soars), have sold over 70 million copies (Ożóg, 2018) with OUP's English File (Latham-Koenig, Oxenden, & Lambert) selling over a million copies in China alone. Generally speaking, it is taken for granted that commercial publications in the educational sector are based on sound, accepted pedagogical principles. Early language teaching publications (from the 1950s onwards) naturally reflected practices that were thought to promote language learning at that time – such as repetition, drills and sentence-level grammar exercises. As our understanding of language learning developed, this Structural approach gave way to a Communicative one, reflecting the 1970s preoccupation with the importance of communicative competence, influenced by theorists such as Hymes (e.g. 1972) and Halliday (e.g. 1975). This approach remains the predominant one (in the West at least) 50 years later. It represents, remarkably perhaps, the last time that applied linguistics substantially influenced a language teaching approach, or at least, one that had such global reach and enduring influence. Since then, findings from the fields of applied linguistics and second language (L2) acquisition, which should have fed into language learning approaches and hence language coursebooks, have been slow to do so in any systematic or significant way. Where they have, the way in which language learning theory 'translates' into pedagogy in the coursebook and thence classroom, can be questionable. In parallel with this is the problem of the socio-cultural standpoint of teaching materials of an international language such as English, issuing from a particular geographic heartland, viz. England. As with applied linguistics and L2 acquisition research, developments in sociolinguistic, socio-cultural and socio-political theory have been realised in language teaching coursebooks only as a rather superficial multi-cultural gloss. The advent of 'global' coursebooks conceived in the 1990s, with multiple iterations, attempting to capture international appeal, still has not resolved the conundrum that language – and hence language teaching materials, that is, the combination of content and pedagogy – constitute cultural artefacts, imbued with cultural values and ideologies. All in all, as Timmis, Mukundan, and Alkhaldi laconically observe: 'for such commonplace objects, [coursebooks] have aroused a surprising degree of controversy' (2009, p. 11). These then, are the chief areas of contention that I will develop in this article. Opposing these issues, it will be acknowledged that coursebooks remain the default language learning resource, and that teachers and learners world-wide need, want and value them as ready-made language teaching materials.